Comparison Of FLC And ANFIS Method To Keep Constant Voltage Based On Flyback Converter - Nismayanti, Nila Nanda; Sudiharto, Indhana; Yanaratri, Diah Septi (Politeknik Negeri Ujung Pandang, 2022)
The development of tecnology suggest humans to always create certain types of renewable inovation, which are usefull for public facilities. Especially in information technology we always need to do the things like work, school and etc using gadget. To reduce various kind of problems on battery health, needs an inovation about charger station in public places. This charger station has a single input single output system so that using just 1 battery source can be used for charging. To realize this charging system, a flyback converter that is capable of working with single input single output is used, which is of course controlled by the Adaptive Neuro Fuzzy Inference System (Anfis) so that the resulting output voltage remains constant, which is 19 V